Hypertext and journalism: Reality and further research - Díaz-Noci, Javier (Anuario ThinkEPI, 2018)
In the initial literature devoted to online journalism the use of hypertext was studied; however, this topic has received little attention since then. Nevertheless, in the last few years there has been renewed interest from several points of view. At the same time, inconsistencies in the application of hypertext criteria in news reporting has been observed. In this article we discuss the current state of the topic of hypertext in journalism.
Keywords: Hypertext; Online journalism; Communication; Decision making; Qualitative methods.